Investigating the Impact of Demographic Characteristics on Encouraging Public Donations via SMS Advertising - M. H. Hosseini; S. Hajizadeh; B. Hassanpour (تحقیقات بازار یابی نوین, 2011)
This study has been conducted to investigate the effects of demographic characteristics including age, gender, marital status, education level, occupation type, and income level on encouraging public donations through advertising via SMS service in order to evaluate the effects rate of these elements on individuals’ attention and measure/action factors. The research is based on data obtained by distributing the questionnaire among 560 individuals who have formed the sample size of this study. The dependent variable of donation attraction has been analyzed along with two indices of attention and action, which are regarded as its measurement criteria. Therefore, the effects rate of demographic factors on these two parameters has been investigated. It is noteworthy that the analysis of collected data was done by SPSS software. The results have determined specific boundaries for people in sending SMS in order to encourage public donations. For instance, how many people among the sample size of this research will pay attention to the messages, how many of them are potential donators, and which individuals and groups have been identified as real executives.